Designing and implementing an educational framework for advanced paramedic practitioners rotating into primary care in North Wales. Issue 5 (3rd September 2021) - Eaton, Georgette; Happs, Ian; Tanner, Rob
ABSTRACT: Background: Rotational working has been offered as a solution to bridge the retention crises faced by ambulance services in the United Kingdom due to the inception of paramedics working in primary care. One project in North Wales examines the viability of rotating Advanced Paramedic Practitioners employed by Welsh Ambulance Services NHS Trust into primary care. As part of this project, an educational framework was developed to prepare and support Advanced Paramedic Practitioners in the provision of clinical care in primary care settings. This educational framework was evaluated to determine how it supported the development of Advanced Paramedic Practitioners in the primary care setting. Methods: Semi-structured focus groups were undertaken with Advanced Paramedic Practitioners (n = 7) and GP trainers (n = 4). Outcome: A narrative analysis of the information collected highlighted three overarching themes concerning the need for clinical supervision and feedback in primary care, and the usefulness of the education framework in regard to a tailored curriculum and recording progression. Discussion: Despite the upcoming workforce changes, there is currently no standard education framework to support the development of Advanced Paramedic Practitioners in primary care. This evaluation offers insight into the educational needs of Advanced Paramedic Practitioners working in this setting and suggests an education structure that can best support their learning, whilst meeting regulatory requirements for paramedic professional development. Formal research is required to determine any link between provision of education for Advanced Paramedic Practitioners in primary care and patient outcome and safety.